High genetic connectivity in a scleractinian coral (Lobophyllia corymbosa) around Sulawesi, Indonesia - Widyastuti Umar; ASMI CITRA MALINA A.R. TASSAKKA; JAMALUDDIN JOMPA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Umar W, Tassakka ACMAR, Jompa J. 2019. High genetic connectivity in a scleractinian coral (Lobophyllia corymbosa) around Sulawesi, Indonesia. Biodiversitas 20: 3484-3492. The life cycle of scleractinian corals begins with a pelagic larval phase subject to the influence of currents, with the potential to disperse propagules over vast geographical distances. We investigated the mitochondrial COI genome to investigate genetic population structure and potential biophysical barriers (in particular water mass movements) that could affect connectivity between populations in the seas around Sulawesi, in the Indonesian Coral Triangle. Lobophyllia corymbosa was selected as representative of corals with a broadcast spawning reproductive strategy and relatively long Pelagic Larval Dispersal (PLD) period. Analysis of mtDNA sequences from 103 colonies collected at depths of 3 to 10 meters in 4 locations (Manado, Toli-Toli, Spermonde, and Wakatobi) resulted in FST = 0.00632, indicating no genetic isolation or significant differentiation. The tendency towards genetic homogeneity across the entire population indicates that gene flow has been maintained, most likely through widespread dispersal of propagules within the study area. The dominant surface flow directions recorded during the reproductive period of this species provide support for this gene flow model, as the currents could enable dispersal and recruitment patterns maintaining connectivity between L. corymbosa populations around Sulawesi.